Legal aspects of judicial protection of exclusive rights to digital assets - Belova A. A. (Topical issues of law, economic and management, 2025)
The article is devoted to the study of legal conflicts arising in the context of judicial protection of exclusive rights to digital assets. The author analyses the peculiarities of qualification of such objects as cryptocurrencies, big data, 3D models and virtual game property, based on Russian and foreign judicial practice. The case of VKontakte v Double Data (2021) is considered, demonstrating the contradictions between the extraterritoriality of digital assets and the territoriality of jurisdictions. Particular attention is paid to the problem of distinguishing digital assets from intellectual property, as well as the dual status of virtual property. Finally, a classification of digital assets into three categories is proposed: protected intellectual property, virtual gaming property and crypto-assets. It emphasises the need to adapt legal norms to digital realities while maintaining a balance between innovation and protection of rights holders.
Keywords: Big Data; Big Data; cryptocurrencies; авторское право; большие данные; цифровые активы; криптовалюты; digital assets; судебная защита; judicial protection; исключительные права; copyright; 3D-модели; виртуальное имущество; правовые коллизии; exclusive rights; 3D models; virtual property; legal conflicts